Lexical Variation of the Karo Language in Karo Regency: Dialectological Study - Wahyu Setiawan; Dwi Widayati; Sugihana Sembiring (JALC : JOURNAL OF APPLIED LINGUISTIC AND STUDIES OF CULTURAL, 2024)
" Lexical variation is a different form of lexicon from the same dialect, and its origins can be traced based on the distribution of language users. This research aims to describe the lexical variations that exist in Karo Regency. The theory used is the theory of structural dialectology. The data collection method used in this research is using the skill method and note-taking method. The data analysis method used is the matching method, with the basic technique of selecting certain elements. Then the matching method is continued with mapping and the dialectometry method. The results of this research are 48 words that have lexical variations from the 200 Swadesh vocabulary lists in the research area, namely in the glosses ash, smoke, good, burnt, lots, wet, split (me-), true, swollen, heavy, swim, big, flower, bad, worm, kiss, wash, meat, with, there, push, tail, dig, rub, mountain, hit, delete, liver, suck, count, fish, tie, sew, fall, word (ber- ), flea, other, hold, think, navel, white, day, pull, laugh, tits, sleep, and blunt. Mapping of lexical variations in this study shows that there are more lexical variations in observation areas 3 and 4, namely the Simpang Empat and Naman Teran subdistricts. The status of lexical differences in the Karo language based on dialectometric analysis shows that Barusjahe District, Tigapanah District, Simpang Empat District and Naman Teran District speak the same dialect.”